2019
DOI: 10.14202/vetworld.2019.1422-1427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immune responses of pups following modified live virus vaccinations against canine parvovirus

Abstract: Background and Aim: Canine parvovirus (CPV) is the most important viral cause of enteritis and mortality in pups. Evaluation and monitoring of pre- and post-vaccine immune responses may help to determine the efficacy of the current vaccination schedule being followed in pups in India. This study aimed to evaluate and monitor the pre- and post-vaccine immune responses of CPV vaccinated pups using hemagglutination inhibition (HI) assay. The neutralizing antibody titer levels were also detected using serum neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Besides, there are several factors that affect on vaccine response including high MDA titer, vaccine storage conditions and failure to maintain a cold chain [ 24 ], the presence of parasitic diseases that can reduce nutrition then causing immunosuppression and stress [ 25 ]. Thus in this study, all puppies have treated with anthelminthic drugs twice before the beginning of the study, and the most important factor is MDA, which can interfere with modified live virus and cause vaccine failure [ 26 ]. Generally, MDA is known as the first defense against pathogens in puppies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are several factors that affect on vaccine response including high MDA titer, vaccine storage conditions and failure to maintain a cold chain [ 24 ], the presence of parasitic diseases that can reduce nutrition then causing immunosuppression and stress [ 25 ]. Thus in this study, all puppies have treated with anthelminthic drugs twice before the beginning of the study, and the most important factor is MDA, which can interfere with modified live virus and cause vaccine failure [ 26 ]. Generally, MDA is known as the first defense against pathogens in puppies.…”
Section: Discussionmentioning
confidence: 99%
“…The original prototype CPV-2 is no longer present in canines but is available only in CPV vaccines [15]. Previous studies in India have identi ed the CPV-2a variant as the dominant strain with few reports of CPV-2b variant and CPV-2c [11,12,[16][17][18][19][20]. But few recent studies have reported increased occurrence of CPV-2c in various neighbouring countries like China, Taiwan, Myanmar and Thailand [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Since the specific host ranges of canine and feline parvoviruses are primarily controlled by the ability of the capsid to bind the TfR, mutations in the receptor binding site alter the ability of the virus to infect different hosts 3 , 8 , 9 . Importantly, the site of TfR binding overlaps on the capsid surface with known antigenic epitopes, so that many mutations alter both antibody recognition and host range 10 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Typically CPV is a potent antigen that gives rise to high levels of antibody after infection 17 – 19 . In addition, the live virus immunization is provided to puppies followed by a series of booster shots 10 , 20 . In dogs and cats, the antibodies that are produced against the capsids of CPV and FPV efficiently protect against infection in recovered or vaccinated animals.…”
Section: Introductionmentioning
confidence: 99%